Socioeconomic inequality in the co-occurrence of anemia and stunting among adolescent girls aged 15–19 years in Sub-Saharan African countries: a decomposition analysis - Tewodros Getaneh Alemu; Elsa Awoke Fentie; Daniel Gashaneh Belay; Desale Bihonegn Asmamaw; Ever Siyoum Shewarega; Wubshet Debebe Negash; Habitu Birhan Eshetu; Fantu Mamo Aragaw; Samrawit Mihret Fetene; Rediet Eristu Teklu (BMC Public Health)
Abstract Introduction Undernutrition, particularly stunting, and deficiency of micronutrients are prevalent nutrition-related problems in adolescent girls residing in low- and middle-income countries. The coexistence of both kinds of malnutrition typically impacts the most vulnerable people, such as women of reproductive age, and it has a detrimental impact on maternal and child health. Besides, malnutrition and inequality form a vicious cycle that is hard to break without all-encompassing solutions that address every stage of the life cycle. Therefore, this study aimed to assess the presence of socioeconomic inequality in the co-occurrence of anemia and stunting and its contributors in sub-Saharan African countries. Methods A total of 39,712 weighted adolescent girl samples from DHS data SSA countries were included in the study. Erreygers normalized concentration index and its concentration curve were used to assess socioeconomic-related inequality in the co-occurrence of anemia and stunting. Decomposition analysis was performed to identify factors contributing to socioeconomic-related inequality. Results The weighted Erreygers normalized concentration index for co-occurrence of anemia and stunting was − 0.046 with Standard error = 0.0043 (P value < 0.0001); indicating that co-occurrence of anemia and stunting was disproportionately concentrated among the poor. The decomposition analysis revealed that wealth index, place of residency, adolescent educational level, and unimproved source of water were the major contributors to the pro-poor socioeconomic inequalities in the co-occurrence of anemia and stunting. Conclusion and recommendation In this study, there is a pro-poor inequality in the co-occurrence of anemia and stunting. Therefore, it’s vital to step up initiatives that improve access to education for adolescent girls, supply of safe water, and boost the economic standing of their country to enhance the level of living status of the population.